Improved sleep after Qigong exercise in breast cancer survivors: A pilot study - Wen Liu; Lauren Schaffer; Natalie Herrs; Christine Chollet; Sarah Taylor (Elsevier, 2015)
Objective: Sleep disorder and fatigue are among a few major concerns of breast cancer survivors across the survivorship trajectory. The purpose of this pilot study was to examine feasibility and trends in multiple outcomes after a 6-week Qigong exercise program in breast cancer survivors. Methods: Eight female adults (mean age 55.4 ± 9.4 years, mean time after the completion of cancer treatment 3.9 ± 5.7 years) who had a diagnosis of breast cancer and were at least 3 months postcompletion of primary cancer treatment prior to participation in this study. Baseline evaluation was administered using subjective questionnaires on sleep quality, insomnia, fatigue, and quality of life. All subjects participated in two training sessions to learn the "Six Healing Sound" Qigong exercise and attended group Qigong sessions once per week in the following 6 weeks. In addition to the group sessions, subjects were asked to perform the Qigong exercises twice at home right before going to bed in the evening and immediately after getting up in the morning. Following the 6-week intervention, subjects were re-assessed using the same questionnaires. Pre- and post-intervention scores were analyzed for statistical significance. Results: Compliance rate was 89.6% for group sessions and 78.5% (ranging from 65.6% to 90.7%) for daily home Qigong exercises. No participant reported any adverse event or side effect during the study. All participants indicated in the end-intervention questionnaire that they would highly recommend the intervention to others. Significant improvements were observed in sleeping quality score (from 10.3 ± 3.6 to 5.4 ± 2.3, P < 0.01), insomnia index score (from 16.2 ± 3.2 to 6.8 ± 4.8, P < 0.01), fatigue score (from 60.3 ± 9.4 to 49.1 ± 8.6, P < 0.01), and SF-36 score (from 66.8 ± 7.7 to 80.9 ± 3.9, P < 0.01). Conclusions: Results of this single arm pilot study showed the feasibility and potential of "Six Healing Sounds" Qigong exercise for improving sleep and other symptoms in breast cancer survivors.